The Data integration guide : how to design, deliver, deploy, and sustain efficient data integration solutions in your information system - Fessi, Ahmed ([United States] : Ahmed Fessi, 2022)
The Data Integration Guide is a synthetic book addressing all Data Integration aspects. This book will walk you through Data Integration concepts and features, its business value, as well as the main Data Integration patterns, mechanisms and technical considerations. It will also help you get a better understanding on how to succeed in delivering your Data Integration projects, and sustain the setup during the operations phase. This book aims to guide you through the Data Integration journey, providing you with a complete toolkit that will save you a lot of time and effort to better scope, architect, deliver, and maintain Data Integration projects that provide you access to limitless data capabilities and business value.
The Data Intergration guide -- Chapter 1. Data Integration -- Chapter 2. Benefits & Business Value -- Chapter 3. Terminology, Main Concepts & Features -- Chapter 4. Data Integration Patterns -- Chapter 5. Connectors & Integration Mechanisms -- Chapter 6. Security & Technical Architecture -- Chapter 7. Data Integration Projects -- Chapter 8. Operations Management - Chapter 9. Solution Components -- Chapter 10. Digital Transformations.
Keywords: DATA INTEGRATION